Reply to Discussion on 'Strength and permeability properties of sodium silicate-glyoxal stabilized silt and fine sand' by Mollamahmutoglu et al. 2022 (QJEGH, 55, qjegh2021-115) - Avci, Eyubhan; Mollamahmutoglu, Murat (Geological Soc Publ House, 2022)
[Abstract Not Available]